2001
DOI: 10.1046/j.1365-2222.2001.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase‐1 (HO‐1) protein induction in a mouse model of asthma

Abstract: The expression of HO-1 is increased within the lung tissue in allergic airway inflammation. Measurement of HO-1 activity may be clinically useful in the management of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 38 publications
6
31
0
Order By: Relevance
“…Recent studies demonstrate increased expression of the 32-kDa stress protein HO-1, the principal biological source of CO, in preclinical models of asthma and in human asthma (7,18,21). HO-1 responds to induction by a variety of agents, including ultraviolet A radiation, thiol-reactive substances, nitric oxide, and proinflammatory cytokines (6,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrate increased expression of the 32-kDa stress protein HO-1, the principal biological source of CO, in preclinical models of asthma and in human asthma (7,18,21). HO-1 responds to induction by a variety of agents, including ultraviolet A radiation, thiol-reactive substances, nitric oxide, and proinflammatory cytokines (6,17).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed elevated HO-1 expression in association with preclinical models of asthma and human asthma (7,18,21). Several laboratories also detected elevated levels of CO in the breath of patients with asthma (14).…”
mentioning
confidence: 99%
“…Previous study suggested HO-1 could protect against airway inflammation by down-regulating tumor necrosis factor receptor (TNFR)1 dependent oxidative stress [30] . In asthma particularly, it was considered that the increase of HO-1 expression and activity were protective [31] . The anti-asthmatic effects of Ulmus davidiana var japonica were also found associated with up-regulating airway HO-1 [32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exhaled CO levels are elevated in individuals with asthma (43), and while some studies have shown an increase upon allergen challenge (45) and a decrease with corticosteroids (46), other studies have shown no effect (44). In a murine model of asthma, HO-1 expression is increased in the airway lumen and bronchial submucosa of antigen-challenged mice (47). In addition, Almolki and colleagues recently demonstrated that up-regulation of HO-1 by hemin decreased airway inflammation, mucus secretion, and airway responsiveness to histamine in ovalbumin-sensitized guinea pigs (48).…”
Section: Asthmamentioning
confidence: 99%